Estudio de la condición deportiva del caballo criollo colombiano a partir de la medición de ácido láctico en el criadero Puerto Triunfo (2024)
This project focused on studying the metabolic response of horses during moderate exercise through the measurement of lactic acid levels at different stages in the Puerto Triunfo farm. Data were collected from several equines of different ages, genders, and gaits, analyzing lactic acid levels before, during, and after exercise. The results revealed significant variations in lactic acid levels according to the gender, age and gait of the horses. Males showed higher values compared to females, and a tendency to decrease lactic acid levels was observed as the age of the horses increased. In addition, differences in lactic acid levels are identified between different gaits, suggesting a direct relationship between exercise intensity and lactic acid production. The comparison of the results with the existing literature allowed establishing a connection between lactic acid levels and the metabolic response during exercise in horses. In addition, the importance of considering individual factors when designing training programs and monitoring equine health was highlighted. The recommendations derived from this study point to the personalization of training programs, constant monitoring during exercise, promotion of aerobic capacity, adequate nutritional care, and planning of veterinary care. It is also suggested that future deep investigations into the relationships between lactic acid and other physiological indicators, as well as the influence of environmental factors